On the diversity gain region of the dynamic decode-and-forward relay-assisted Z-channel - Sirigina, Rajendra Prasad (2020)
In an interference-limited system, the interference forwarding by a relay enhances the interference level and thereby enables the cancellation of the interference. In this work, interference forwarding by a half-duplex dynamic decode-and-forward (HD DDF) relay in a two-user Z-channel is considered. In the two-user Z-channel, one user is interference-limited while the other user is interference-free. The diversity gain region (DGR), which characterizes the tradeoff between the achievable diversity orders between the two users, is an appropriate performance metric for the Z-channel. Closed-form expression for the achievable DGR with the interference forwarding by the HD DDF relay is presented. The multiplexing gain regions (MGRs) where the HD DDF protocol achieves better DGR over the direct transmission scheme, full-duplex decode-and-forward (FD DF) and FD partial DF relay assisted Z- channel are identified. The HD DDF protocol is shown to achieve better DGR than the FD DF and FD PDF relay for a large range of MGR. The achievable DGRs for the HD DDF, FD DF, and FD PDF relay-assisted Z-channel and direct transmission scheme are presented for various interference levels and multiplexing gain pairs.